Pengaruh Motivasi terhadap Pembelian Telepon Selular - Murwanto Sigit (Sinergi: Kajian Bisnis dan Manajemen, 2008)
The competition among brands in mobile phone market is getting tight. Dominant players such as Nokia, Erricson, Motorolla, and Siemens now is being challenged by new players which offer a lower price with more attractive design. The purpose of this study is to analyze the effect of price, service availability, technology, and consumer self expression on the motivation to purchase Nokia mobile phone. Another objective is to determine whether there is a significant difference between male and female consumer on each factor. As many as 100 respondents are chosen from Economic Faculty UII students. So far, students is one of potential consumers for Nokia. Multiple regression and test of mean difference has been utilized to analyze data. The result shows that service and technology is significant, meanwhile price and consumer self expression is not significant. This result confirms the current image of Nokia as a good quality brand with stable market. There is significant different between man and woman consumers in all factors.Keywords: service availability, service technology, self expression, motivation